The Imperative for Productive Waqf at the Great Mosque of Semarang in Promoting Community Economic Development - Resha Zulfuaedah, Resha Zulfuaedah; Arief Budiman, Achmad Arief Budiman; Ali Maskur, Ali Maskur; Rosikhan Anwar (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2025)
Productive waqf represents an innovative model for optimizing waqf assets to strengthen social and economic resilience within Muslim communities. Despite its significant potential, the implementation of productive waqf in Indonesia remains limited, particularly in mosque-based institutions that often face challenges in professionalism and governance. This study aims to analyze the management system of the Wakaf Produktif Center (WPC) of the Great Mosque of Semarang, focusing on the implementation of nazhir’s rights and obligations and its impact on community welfare. A descriptive qualitative approach was employed, grounded in the good waqf governance framework. Data were collected through semi-structured interviews with WPC administrators and shop tenants, field observations, and official document analysis. Data analysis followed the Miles and Huberman model, including data reduction, display, and verification. The findings reveal that WPC management aligns with Law No. 41 of 2004 on Waqf, emphasizing professionalism, accountability, and transparency. Productive waqf assets such as shop rentals and culinary centers have generated sustainable income that supports mosque programs and enhances the economic well-being of the surrounding community. The novelty of this research lies in identifying a replicable mosque-based productive waqf governance model adaptable to other regions. Scientifically, this study contributes to the development of a practical good governance model for productive waqf management in Indonesia. Future studies are recommended to examine the long-term effectiveness of the WPC model and employ quantitative approaches to measure its economic impact on beneficiaries.